2021
DOI: 10.1029/2021gl094908
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of Wildfires Impact on Air Quality Exceedances During the 2020 Record‐Breaking Wildfire Season in the United States

Abstract: Biomass burning (BB) emits a large quantity of aerosols and trace gases into the atmosphere, often leading to hazardous air quality and health problems (Koning, et al., 1985). In the summer of 2020, the western United States experienced a record-breaking wildfire season. A series of large wildfires, fueled by accumulated biomass, heatwaves, and dry winds, burned more than 10.2 million acres. These wildfires spread rapidly and destroyed several small towns in California, Oregon, and Washington. According to MOD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…The identification of long-range smoke is supported by HRRR-Smoke simulations, which show that smoke during this period largely resulted from fires in Northern California (∼1500 km from Boulder, Figure S5). California experienced a historic fire season in late 2020, 16 notably including the August Complex fire that burned over 1 million acres. While NO x remained relatively constant through each period, regional O 3 and CO mixing ratios increased during the local smoke period followed by larger increases during the long-range transported smoke period.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of long-range smoke is supported by HRRR-Smoke simulations, which show that smoke during this period largely resulted from fires in Northern California (∼1500 km from Boulder, Figure S5). California experienced a historic fire season in late 2020, 16 notably including the August Complex fire that burned over 1 million acres. While NO x remained relatively constant through each period, regional O 3 and CO mixing ratios increased during the local smoke period followed by larger increases during the long-range transported smoke period.…”
Section: Measurementsmentioning
confidence: 99%
“…A statistical analysis of fires between 1984 and 2018 indicate a doubling of fire events within the last half of this period and a quadrupling of the median annual area burned for the western United States . These trends have significantly impacted air quality in the last two decades, for example with well-documented increases in particulate matter. …”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric chemical transport models (CTMs) offer one common approach to linking wildfire activity to concentrations of key pollutants and downstream human impacts, but their use faces a number of difficulties . First, uncertainties in wildfire emission inventories have been shown to lead to substantial differences in CTM-estimated smoke PM 2.5 concentrations, with up to 20-fold differences in estimated regional wildfire-attributed PM 2.5 concentrations when different leading inventories are fed into the same transport model, although recent efforts have shown that satellite-based emission calibration can improve the simulation accuracy . Second, the complex chemistry regimes during wildfire (in particular, production of organic aerosols) and hyperlocalized meteorology are often not well-captured by CTMs, leading to concerns over their ability to correctly model the transport of wildfire smoke. Third, parameterized heights of plume injections and the vertical allocations of emissions differ considerably across different CTMs and often compare poorly with observed injection heights, leading to discrepancies in surface PM 2.5 concentrations when compared with in situ observations. , …”
Section: Introductionmentioning
confidence: 99%
“…Wildland fires are responsible for an increasing number of days exceeding NAAQS levels across the US at PM 2.5 monitor locations ( 11 ). The majority of PM-related health impacts in the U.S. may be attributable to wildland fires in future years due to continued reductions in anthropogenic emissions combined with climate-related increases in wildland fire emissions ( 12 ).…”
Section: Changing Conditions In Ambient Pm 25 In T...mentioning
confidence: 99%